Impact of a New Home Care Payment Mechanism on Growth of the Home Care Workforce in Taiwan. (25th January 2021) - Wu, Shih-Cyuan; Peng, Mei-Chi; Hsueh, Jui-Yuan; Chiang, Tung-Liang; Tu, Yu-Kang; Tung, Yu-Chi; Chen, Ya-Mei
Abstract: Background and Objectives: Taiwan implemented its first National 10-Year Long-Term Care Plan in 2008 and its second in 2017. Over the first 10 years, the number of home care workers grew too slowly to meet demand. To increase the home care workforce, the government introduced 2 new payment mechanisms in 2018. This study assesses these mechanisms' impact on growth in numbers of home care workers and use of home care services in Taiwan. Research Design and Methods: Data were collected from the Ministry of Health and Welfare (2014–2019) and the Division of Long-Term Care (2017–2019). Generalized estimating equations compared rates of growth in the number of home care, institutional care, and foreign care workers and the number of care recipients receiving care from each group before and after 2018. Results: Before 2018, rates of growth in all three groups of care workers increased slowly. After 2018, the rate of growth for home care workers increased to 31.8% from 9%, while growth in the other two groups remained stable. While there was greater workforce growth among home care than institutional care workers post-implementation of the payment mechanisms ( p < .05), the number of home care recipients ( p < .05) and monthly home care visits ( p < .05) also increased. Discussion and Implications: The new payment mechanisms improved home care workers' autonomy and salaries and appear to have contributed to immediate increased recruitment and retention. Whether this increase continues over the long run will need to be determined.